Acute stomach volvulus: Total gastric necrosis - Campos Pierri, Néstor; Andrade, Eduardo; Da Rosa, Eduardo; Bentancurt, Bernabé; Decoud, Susana (Cirugía del Uruguay, 1986)
Presenting a case of acule volvulus of stomach with total gastric necrosis requiring complete gastrectomy with a favorable evolution. The case is discussed and accompanied with a clinical, etiological, diagnostic and therapeutic analysis of this uncommon affection.